#TITLE_ALTERNATIVE# - SUDJANA (NIM 26990001), ENUNG
Cracking at the surface of the bituminous layer of a road pavement is a widespread problem in regions of high ambient temperature, and has been found to correlate closely with hardening of bitumen, caused largely by oxidation and volatilization of the lighter fractions in the bitumen. As a consequence of bitumen hardening, the bituminous mix becomes more susceptible to traffic and non-traffic associated cracking. In Indonesia, bitumens used in road construction are supplied from a number of sources and are imported to supplement material produced locally. Bitumens of the same grade from different sources vary, sometimes significantly, thus bitumens from various suppliers may satisfy the penetration requirement, but show wide divergence where temperature susceptibility and/or resistance to hardening during handling and in service are concerned. Additives are sometimes introduced into bituminous mixes to improve some aspects of performance and studies have shown that hydrated lime can reduce the rate at which bitumen hardens as a consequence of oxidation. The properties of samples of 80 pen grade bitumen from different sources currently supplying the Indonesia road construction industry have been investigated. Sample from two sources, which were determined as having potentially the greatest and least susceptibility to hardening, were selected to be blended with hydrated lime and benzene, as the solvent, by the procedure of Plancher et al. It was found that processing of bitumen with lime indicated an improvement in the resistance to hardening measured in tests of the penetration, ring and ball softening point temperature, ductility, specific gravity, solubility, flash point, and according to relationships between viscosity and temperature. The residue from thin film oven testing (TFOT) was subjected to continuous heat treatment and progress of hardening monitored at different periods. This showed that there was a tendency for hydrated lime to delay the hardening process of bitumens, from more than 25 hours for unprocessed bitumen to more than 50 hours for processed bitumen.